1993
DOI: 10.1212/wnl.43.1_part_1.106
|View full text |Cite
|
Sign up to set email alerts
|

Clock‐drawing test and unilateral spatial neglect

Abstract: We investigated the ability of 25 patients with left unilateral spatial neglect to make a clock face by putting numbers inside a printed circle. Impairment seen in this clock-drawing test did not parallel neglect severity as judged by results of the line-cancellation and line-bisection tests, as well as the copying of a daisy. The score for clock drawing correlated highly with the verbal WAIS score. Most neglect patients with a verbal IQ of 87 or more could draw a clock face fairly well and used planning in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 0 publications
0
43
1
Order By: Relevance
“…The test has also been documented to be the most sensitive ofthe 15 BIT subtests at detecting visuospatial neglect (Halligan et al, 1989). Ishiai et al's (1993) study showed that cancellation tasks or Une bisection tasks were a better indicator of neglect than drawing tasks. The inclusion of a distractor in the Star Cancellation task results in increased sensitivity of this particular subtest.…”
Section: )mentioning
confidence: 88%
“…The test has also been documented to be the most sensitive ofthe 15 BIT subtests at detecting visuospatial neglect (Halligan et al, 1989). Ishiai et al's (1993) study showed that cancellation tasks or Une bisection tasks were a better indicator of neglect than drawing tasks. The inclusion of a distractor in the Star Cancellation task results in increased sensitivity of this particular subtest.…”
Section: )mentioning
confidence: 88%
“…The CDT tests visuoconstructive ability and executive function, and also involves numerical and verbal memory (Shulman et al, 1986;Kirk and Kertesz, 1991;Ishiai et al, 1993). Most studies of the CDT in dementia have produced sensitivities within the range of 78% to 100% and speci®cities of 87% to 100% (Wolf-Klein et al, 1989;Tuokko et al, 1992;Mendez et al, 1992;Brodaty and Moore, 1997;Esteban-Santillan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, the performance in the clock drawing test correlated with the verbal IQ in the Wechsler adult intelligence scale (WAIS) in patients with left USN [6]. In this report, the patients with higher WAIS verbal IQ made better performance in drawing dial in the clock, even though they had a left USN.…”
Section: Discussionmentioning
confidence: 48%